Diversity management and the presumptive universality of categories: the case of the Indians in Singapore. Issue 1 (1st January 2019) - Jain, Ritu; Wee, Lionel
ABSTRACT: Increasing societal and linguistic diversity poses significant challenges to formative categories of language policies. We make this point via an examination of Singapore's management of its most linguistically diverse ethnic group, the Indians. While heterogeneity has always been Singapore's defining feature, the nature and scale of recent immigration have resulted in an unprecedented societal complexity. The government's appreciation of this complexity among the Indians has led to a relaxation of the education policy by which five other Indian languages (Bengali, Gujarati, Hindi, Punjabi, Urdu) serve as possible alternatives to Tamil (the officially assigned ethnic mother tongue). However, speakers from these other Indian language communities often prefer Hindi over alternatives. The growing prominence of Hindi illustrates that progressive policies can nonetheless be subverted by the very groups they seek to empower. We analyze this policy predicament, tracing the roots of Singapore's language policy to categories inherited from British colonialism. Consequently, contemporary tweaks to the policy leave unchallenged the presumptive universality of these categories. Calling for consistent attention to the situatedness and provenance of all categories (northern as well as southern), we close our paper with a description of what Singapore's language policy vis-à-vis the Indian communities would look like from a decolonial perspective.